Efficacy of Thuthikeerai in Moola Noi - Sounthararajan, K.; Sivarangini, S. (1st International Symposium on Traditional Medicine | 2014, 2014)
The objective of the study is to evaluate the efficacy of Thuthikeerai in Moola Noi. It is a quasi experimental study. This study was carried out in a Private Siddha Medical clinic at Kaithady for one year using 32 patients from both sexes between 20-60 years old. Patients who have come with constipation, painful swelling and often accompanied by itching or irritation near the anal region and who have come with painless rectal bleeding were selected for the study. The patient's verbal consent was taken. Patients with prolapsed Ulmoolam, pregnancy, Diabetes mellitus, wheezing and hypertension were excluded in the study. The patients who have come with the above mentioned sign and symptoms were guided by the researchers to use the Thuthikeerai as a dietary supplement in the form of Varai for every day with lunch and is fried with castor oil and applied over the affected area as a poultice for 4 weeks. Subjects were not allowed to seek therapy from any other alternative medical system. The selected patients were asked to avoid spicy and hot foods. The treated patients were instructed to visit the clinic in every 3 days for three visits, then advised to visit in once a week for 3 times. The changes in the disease and progress of signs and symptoms were recorded. This study revealed that 24 patients out of 30 were suffered from constipation, painful swelling, often accompanied by itching or irritation near the anal region and others had painless rectal bleeding. 18 patients out of 24 were completely relieved from signs and symptoms at the treatment. 4 had moderate, I mild relief and 1 no improvement. In out of 6 patients 4 had complete relief, I moderate and 1 no improvement. Two patients were not co-operated. The complicated patients were referred to further management. This study concludes that the Thuthikeerai which was used as dietary supplement and external medicine for Moola Noi had shown better relief and no side effects.
Keywords: Thuthikeerai; Moola Noi; Varai; Poultice; Ulmoolam